PENDEKATAN PSIKOANALISIS DALAM CERPEN PELAYATAN KARYA D. WIDYA P. - Puji Lestari; Ardian Rendra Permana; Eva Dwi Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to describe the personalities and forms of attitudes and actions carried out by several characters in the short story entitled Pelayatan by D Widya P. The method used in this research is a hermeneutic approach. Data was obtained using reading and note-taking techniques. The results of the research show that there are aspects of id, ego, superego shown by the characters in this short story in social and social life. Id, Ego and Superego are important elements in the structure of human personality. The id, ego, and superego work together to create patterns of human behavior. Where the Id provides natural human needs, the ego connects personal needs with reality, and the superego adds moral value to every human behavior. This third aspect is explained again and proven by a text quote from the novel which states that the Id which is related to the text quote in the novel is the biological aspect in the form of lust and sexual passion and works according to pleasure and satisfaction, Ego is the aspect that works based on needs and desires. . in accordance with the principles of reality in a person, while the superego is a change in action that adapts to moral values ​​or behavior that is in accordance with the norms that apply in society